Acute cerebellar ataxia: differential diagnosis and clinical approach - Pedroso, José Luiz; Vale, Thiago Cardoso; Braga-Neto, Pedro; Dutra, Lívia Almeida; França, Marcondes Cavalcante, Jr; Teive, Hélio A. G.; Barsottini, Orlando G. P. (Arquivos de Neuro-Psiquiatria, 2019)
Cerebellar ataxia is a common finding in neurological practice and has a wide variety of causes, ranging from the chronic and slowly-progressive cerebellar degenerations to the acute cerebellar lesions due to infarction, edema and hemorrhage, configuring a true neurological emergency. Acute cerebellar ataxia is a syndrome that occurs in less than 72 hours, in previously healthy subjects. Acute ataxia usually results in hospitalization and extensive laboratory investigation. Clinicians are often faced with decisions on the extent and timing of the initial screening tests, particularly to detect treatable causes. The main group of diseases that may cause acute ataxias discussed in this article are: stroke, infectious, toxic, immune-mediated, paraneoplastic, vitamin deficiency, structural lesions and metabolic diseases. This review focuses on the etiologic and diagnostic considerations for acute ataxia.
Keywords: Cerebellar ataxia; cerebellum; cerebellar diseases